Perception about Islam, attitude, subjective norms, and behavioural intention in using artificial intelligence among university students - A.Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha (IIUM Press, 2025)
Artificial intelligence has increasingly received attention and wide acceptance among university students throughout the world. For Muslims, their behavioural intention in using artificial intelligence ethically is expected to be guided by Islamic teachings. Yet, little is known about the use of artificial intelligence among Muslim students of higher educational institutions. The present study explores how Muslim university students’ perception about Islam, attitude, and subjective norms influence their behavioural intention towards using artificial intelligence in the context of Malaysia. This work extends the understanding of the influence of Islam on Theory of Reasoned Action (TRA) to better explicate one’s behavioural intention in using artificial intelligence. A total of 406 university students in Klang Valley, Malaysia participated in a cross-sectional survey conducted over a three-month period. Perception about Islam, attitude towards using artificial intelligence, and subjective norms were used as the independent variables, while behavioural intention to use artificial intelligence served as the dependent variable. Findings indicate a positive and significant relationship between each independent variable and behavioural intention to use artificial intelligence. Attitude towards AI emerged as the strongest predictor of intention to use AI, while perception on Islam becomes the weakest predictor. This study enhances theoretical insights into technology adoption from the perspectives of TRA and Islamic principles, while also providing practical guidance for developing ethically grounded AI practices within Muslim-majority educational contexts